IMPLEMENTATION OF INTERNET OF THINGS (IOT) FOR TEMPERATURE AND HUMIDITY CONTROL IN WATER SPINACH (IPOMOEA AQUATICA) CULTIVATION - Annisa Risqi SKW; Supriyade; Nursohit; Universitas Salakanagara (RADJA PUBLIKA, 2025)
Kangkung (water spinach) cultivation requires a stable environmental condition to ensure optimal growth, especially in terms of temperature and humidity. In Tangerang Regency, the annual average temperature ranges from 24°C to 32°C with humidity between 73% and 93%, which aligns well with kangkung’s ideal growing temperature of 25°C–30°C. This research designs an automated system based on the Internet of Things (IoT) integrated with an aquaponics concept to control temperature, humidity, and water quality in kangkung cultivation. The system employs a waterproof DS18B20 temperature sensor to measure water temperature, a DHT11 sensor for ambient temperature and humidity, and additional pH, TDS/EC, and turbidity sensors to monitor water quality. Water level is detected using an HCSR-04 ultrasonic sensor. All data is transmitted in real-time through an ESP8266-01 module and can be monitored via LabVIEW on a laptop or through a smartphone. The system also includes an automatic water pump, solenoid valve, and a servo-based auto feeder for the fish. Experimental results indicate the system maintains environmental stability with an average temperature reading error of ±0.5°C and humidity error of ±0.776%. This smart monitoring and control system significantly improves efficiency, accuracy, and the overall quality of kangkung cultivation, especially in tropical climates. The integration of IoT in this aquaponic system offers a sustainable and environmentally friendly solution for modern urban agriculture.